Large-scale GWAS of strabismus identifies risk loci and provides support for a link with maternal smoking - Weixiong He; Peter J. van der Most; Jue-Sheng Ong; Liang-Dar Hwang; Yeda Wu; Morten S. Magnø; Jelle Vehof; Kristi Krebs; Laura Mauring; Katrin Õunap; Erik Abner; Nicholas G. Martin; et al. (Nature Communications)
Abstract Strabismus is a common pediatric eye misalignment and has complex genetic and environmental causes. Previous genome-wide association studies (GWAS) encountered difficulties in identifying strabismus risk variants due to heterogeneity and small samples. We performed large meta-analyses of 11 European-ancestry GWAS (7 sources), analysing broad strabismus (20,464 cases, 954,921 controls) and subtypes (esotropia/exotropia). We discovered 4 loci (e.g., NPLOC4-TSPAN10-PDE6G-FAAP100, COL6A1) for strabismus and 5 additional loci (e.g., CHRNA4, MAD1L1) for strabismus subtypes and we successfully replicated the previously reported strabismus variant near NPLOC4-TSPAN10-PDE6G-FAAP100. Using mendelian randomisation, we found genetic evidence supporting maternal smoking as a causal risk factor for strabismus in offspring.